FRUIT AND VEGETABLE SECTOR OF AGRICULTURE IN THE YEARS OF INDEPENDENCE: DEVELOPMENT, CHALLENGES AND RESULTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article focuses on the state support of the agricultural fruit and vegetable sector during the years of independence, as well as the existing problems in this area and their solutions.